P256 COMORBIDITY ROLE IN THE REOCCURRENCE OF HEART FAILURE EXACERBATION ON A POPULATION OF PATIENTS WHO HAVE A DEDICATED FOLLOW UP. (18th May 2022) - De Masi De Luca, G; Longo, S; Barba, F; Marzo, S; Mauro, R; Accogli, M
Abstract: Background: With this work we drew attention on the importance of a proper FUP dedicated to patients affected by heart failure (HF), while also underlining the importance of proper and efficient management of comorbidities. Material and Methods: 164 patients were put into the FUP program for HF at Cardiology Department in "Card. G.Panico Hospital" in Tricase (Lecce, IT) and with the same organization at "Cardiomed Centre" in Maglie (Lecce, IT) 61% of the patients had just been hospitalized, 24% came from a generic clinic, 15% from the ER. 59% presented a systolic HF, diastolic genesis for the other patients left. The average age was 69±21 year old. During the evaluation of admission to the FUP program, the patients were divided into patients at high, medium and low risk, based on their clinical situation regarding the risk of events. Each risk category had its own different FUP iter, which was both clinical and telemedical, commited to the clinical nurse. During the periodic call, the nurse set, where necessary, a stability judgment after confronting FUP parameters, and showed the report, or better to say, the alerts, to the medical staff who had the role of re–evaluating the patient in order to put in place proper therapeutic measures. Results: In a 12 month FUP period of time 78 alerts have been highlighted. In 64% of the cases it was about weight gaining; in 54% an increase in Borg scale index; in 37% it was due to a reduced Spo2 during exercise; In the following clinical evaluations, in 91% of the cases correctional therapeutic measures have been put into place, consisting of: – diuretic therapy readjustment for os (31 cases); – start of transitory period diuretic therapy for ev (19 cases); – hospitalization (3 cases); – comorbidities correction (59 cases). This last parameter got most attention: in 23 cases it was highlighted a reduction of a % of transferrin saturation by less than 10%, then adjusted (target according to guidelines: >20%); in 17 cases we noticed a clinical situation of bronchial inflammation; in 19 patients showed a worsening in kidney function index. Conclusion: Our experience in the clinic dedicated to heart failure suggests how fundamental attention to comorbidity is, especially where instability can be considered a predicting alert of re–exacerbation of HF.